O026 Effect of oral appliance therapy on OSA endotypes. (9th November 2022) - Osman, A; Naik, G; Tong, B; Chiang, A; Pinczel, A; Rawson, G; Donegan, M; Pitcher, G; Kwan, B; Mukherjee, S; Teare, A; Eckert, D
Abstract: Introduction: Long term CPAP therapy alters OSA endotypes (e.g., reduces loop gain and the arousal threshold). However, while oral appliance therapy (OAT) is known to improve upper airway collapsibility, its effects on non-anatomical OSA endotypes are unclear. Methods: To investigate the effects of OAT on polysomnographic estimates of OSA endotypes we studied 102 people with OSA (AHI=34±20 events/h) pre vs. post-treatment (following 4-6 weeks OAT acclimatization). AHI and endotypic traits were compared between the diagnostic and OAT study visits. Results: OAT reduced the AHI by 50% (30 [25-39] vs. 15 [12-19], median, 95% confidence interval, p<0.01). Passive pharyngeal collapsibility (94 [92-95] vs. 96 [95-97]% eupnea), active pharyngeal collapsibility (98 [95-100] vs. 102 [101-103]% eupnea) and pharyngeal muscle compensation (3.6 [1.2-5.1] vs 4.9 [3.7-6.5]% eupnea) improved with OAT (all p<0.01). The respiratory arousal threshold (116 [114-122] vs. 109 [106-111]% eupnea, p<0.01) and ventilatory response to arousal (31 [28-35] vs. 23 [20-32]% eupnea, p=0.03) decreased. Loop gain did not systematically change overall (0.43 [0.39-0.47] vs. 0.40 [0.38-0.42], p=0.16). However, loop gain reduced in OAT responders (>50% reduction in AHI) (0.42 [0.39-0.45] vs. 0.38 [0.34-0.4] dimensionless, p<0.01). Conclusions: Oral appliance therapy improves upper airway collapsibility and pharyngeal muscle compensation and reduces the ventilatory response to arousal and loop gain in responders. Like CPAP, OAT also decreases the arousal threshold. These findings provide new insight into the mechanisms of improvement in OSA with oral appliance therapy.